AN ISLAMIC EDUCATION PERSPECTIVE ON CHANGE MANAGEMENT IN DEVELOPING ISLAMIC EDUCATIONAL INSTITUTIONS - Mahlani S.; Makmur Harun; Abd Rahman; Wahab (Academic Bright Collaboration, 2026)
This study aims to examine the Islamic education perspective on change management and its role in developing Islamic educational institutions, addressing the need for value based transformation in response to globalization and institutional challenges. This research employs a multidisciplinary library research approach, integrating historical, sociological, theological, philosophical, and pedagogical-managerial perspectives. Data were collected from relevant literature and analyzed using content analysis, discourse analysis, and textual interpretation. The study finds that change management in Islamic education is a structured and systematic approach grounded in the Qur’an, Hadith, and Islamic intellectual traditions. It involves managing key elements such as mindset, leadership, vision, systems, values, culture, and curriculum, as well as internal and external resources. The process includes transforming mindsets, identifying problems, setting goals, communicating vision, implementing change, strengthening commitment, and minimizing resistance. The outputs include institutional value reconstruction, quality education design, and exemplary leadership. This study is limited to conceptual and literature-based analysis, which may restrict empirical generalization. However, it provides a comprehensive theoretical framework for future empirical studies in Islamic educational management. This study offers an integrative framework that bridges Islamic values with modern change management theory, contributing to the development of adaptive, progressive, and value-oriented Islamic educational institutions.